Letter (copy) : Shoes for Spain - Tewson, Vincent
030-0098-001 Secretary' s. HVT/FC/576. Mr. W. Schevenels, 8th August, 1938. The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Mr. Schevenels, SHOES FOR SPAIN. I have now heard from Mr. Chester, Secretary of the National Union of Boot and Shoe Operatives, regarding the despatch of the supply of shoes I mentioned in my letter of the 4th instant. The cases are being sent to Southampton via London for despatch to Rouen to-morrow or Wednesday, and I am enclosing a copy of the instructions we sent for their despatch. I do not know how long the goods will take to get to Cerbere, but probably you will communicate with Mr. Calvet and with Santiago stating that the cases are likely to arrive at the end of the week so that they may make the necessary arrangements. Yours sincerely, Assistant Secretary. Instructions. 292/946/30/98